SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN PEGAWAI DENGAN METODE WEIGHTED PRODUCT BERBASIS WEB - I M. S. D Mahendra; M. A Sudarma; I M. A Suyadnya (Program Studi Teknik Elektro UNUD, 2020)
The development of a company lies in its human resources. The process for obtaining HR (Human Resource) obtained by selecting employees. Koperasi Asi Sedana Luwih is an organization in the economic field that is required for savings and loan services. To get good human resources, the recruitment selection process is carried out in accordance with the criteria needed from each division. To make selection faster and better to minimize DSS (Decision Support System) to help companies get quality human resources. To solve the existing problems, develop DSS using the Weighted Product (WP) method.The decision support system that is generated based on the website and can produce ranking results from each alternative by the Weighted Product method by looking at the results of the largest vector v value of each alternative that can be taken into consideration for companies that allow prospective new buyers. Based on the results of system testing using the blackbox testing method, the output requested by the system is in accordance with the input provided by the user.